2019
DOI: 10.1002/slct.201803965
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐free C5, C7‐Dihalogenation and the Switchable C5 Halogenation of 8‐Hydroxyquinolines

Abstract: The first example on the C5, C7‐dihalogenation of 8‐hydroxyquinolines based on an in situ O‐acyl 8‐hydroxyquinoline formation is realized under catalyst‐free condition in toluene. Modifying the reaction conditions by directly utilizing O‐acylated 8‐hydroxyquinolines in the presence of AlCl3 enables the electrophilic halogenation in the C5 position, leading to the tunable synthesis of C5 halogenated products. The O‐acyl group can be easily removed from the product to provide halogenated quinolines containing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Apart from dihalogenation product ( 133 ), some selective C‐5 halogenations have also been reported with variation in the reaction condition (Scheme 82). The substrate ( 134 )was converted to the product ( 135 )with a mixture of AlCl 3 , TFA and PhI(OAc) 2 .Control experiment [91] established that the mechanistic pathway of dihalogenation went through radical intermediate while mono C‐5 halogenation followed electrophilic pathway via intermediate ( 136 ). The recovery of starting material in case of mono C‐5 halogenation in presence of TEMPO possibly indicated that the NXS was being captured by TEMPO preventing subsequent halogenation.…”
Section: Transition Metal‐free C(sp2)−h Bond Halogenation In Heteroarene Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from dihalogenation product ( 133 ), some selective C‐5 halogenations have also been reported with variation in the reaction condition (Scheme 82). The substrate ( 134 )was converted to the product ( 135 )with a mixture of AlCl 3 , TFA and PhI(OAc) 2 .Control experiment [91] established that the mechanistic pathway of dihalogenation went through radical intermediate while mono C‐5 halogenation followed electrophilic pathway via intermediate ( 136 ). The recovery of starting material in case of mono C‐5 halogenation in presence of TEMPO possibly indicated that the NXS was being captured by TEMPO preventing subsequent halogenation.…”
Section: Transition Metal‐free C(sp2)−h Bond Halogenation In Heteroarene Systemsmentioning
confidence: 99%
“…[hmim]Br DCDPH,NBS Chiral Organocatalyst [56] K 2 S 2 O 8 TBAX or NXS [85] (Cl/Br/I) Electrochemical [74] Acyl chloride [91] NXS (X=Br/Cl/I) AlCl 3 /NXS PIDA (X=Br/Cl) NIS,TFA [46] ArI(OAc) 2 [43] PIDA/NaX [76] (X=Cl/Br/I) NaX NFSI [92] (X=Br/I) NaI,Electrolysis [101] TBAB or TBAC [52] (Pummerer) Erythrosin B, NBS,LED [22] PhI(OAc) 2 or K 2 S 2 O 8 NaBr [38] TXCA [102] ChemistrySelect material in case of mono C-5 halogenation in presence of TEMPO possibly indicated that the NXS was being captured by TEMPO preventing subsequent halogenation. N-flurobenzenesulfonimide (NFSI) was used as an oxidant and sodium salts of halogens (bromine and iodine) acted as halogen source for the halogenation of quinolines (137)and arenes.…”
Section: General Halogenation On Heteroarene Systems Using Different ...mentioning
confidence: 99%
See 1 more Smart Citation